2014
DOI: 10.1590/s0100-736x2014000100001
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco, etiologia e aspectos clínicos da mastite em ovelhas de corte no Paraná

Abstract: Pesq. Vet. Bras. 34(1):1-10, janeiro 2014 1 RESUMO.-A mastite em ovelhas da raça Santa Inês apresenta-se como um problema de grande proporção e gravidade e é dificilmente tratada com sucesso. O objetivo deste estudo foi caracterizar aspectos clínicos, epidemiológicos e etiológicos da mastite clínica em ovelhas de corte criadas no norte do Paraná. O presente estudo foi realizado entre os meses Mastits is infrequent in meat ewes. However Santa Ines ewes have a high incidence of this disease and it is severe and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
8

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
5
14
0
8
Order By: Relevance
“…Predominance of CNS among the microorganisms isolated in the cases of subclinical mastitis (Table 2) is in agreement with that reported by other authors (SPANU et al, 2011;FRAGKOU et al, 2014;PEREIRA et al, 2014). In table 3, the mean values for the milk characteristics of interest are shown according to the sheep breeds and the dry and rainy periods, in the weaning and postpartum stages of the consecutive lactation.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Predominance of CNS among the microorganisms isolated in the cases of subclinical mastitis (Table 2) is in agreement with that reported by other authors (SPANU et al, 2011;FRAGKOU et al, 2014;PEREIRA et al, 2014). In table 3, the mean values for the milk characteristics of interest are shown according to the sheep breeds and the dry and rainy periods, in the weaning and postpartum stages of the consecutive lactation.…”
Section: Resultssupporting
confidence: 89%
“…However, Ciência Rural, v.46, n.10, out, 2016. similar results were reported by PEREIRA et al (2014), although these authors have analyzed clinical mastitis. According to these authors, the period with the highest occurrence of the disease was observed in the beginning of lactation.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Apesar de Pereira et al (23) terem investigado fatores de risco para a forma clínica da mastite e não a subclínica, estes autores defendem que a manutenção de fêmeas doentes junto a sadias pode contribuir para o aumento do número de casos da doença, pois os cordeiros possuem o hábito de mamar em outras ovelhas além da sua mãe, o que pode acontecer também em animais com mastite subclínica. Adicionalmente, outros fatores podem interferir no controle da doença, como um sistema de criação mais intensivo e a ausência de limpeza das instalações, citados também por estes autores.…”
Section: Zafalon Lf Et Alunclassified